Analisa Yuridis Klaim Asuransi Jiwa Secara Ex Gratia Berdasarkan Hukum Asuransi Indonesia - Lendrawati Lendrawati; Kelvin Junnatan (Fakultas Hukum, Universitas Internasional Batam, 2017)
Credit life insurance serves as protection against loan customers, which when credit customers die, the ongoing credit will be paid by the credit life insurance is based on the claim from the heirs of the customer or the bank. Sometimes there are some credit life insurance claims submission rejected by insurers, that will cause problems for the various parties, such as the Bank, that the credit has not been paid off and also the Insured's heirs still have to pay the credit in the bank. The purpose of this research is to seek how the Indonesian insurance law protect the participant which enggage by the insurance police. This research also conducted to anlyze the legal compliance has been applied by PT. Asuransi Himalaya Pelindung. This research is using the normative juridical method of analyzing the laws of Indonesia and Singapore. Sources of data used are in forms of primary legal materials, secondary legal materials and tertiary legal materials. Data collection technique is done through the method of literature study (library research). After all of the data are collected, the data are processed and analyzed. The qualitative analysis is used with the intentions to classify aspects of data studied. Furthermore, it is then concluded that the research associated with this is then described descriptively. Based on this recearch are found that:First, the parties of insurance police are protected based on the their underlying contract.The clause of ex gratia is barely to find in polis agreement, so as long as did’not opposite with their primary contract, ex gratia claim is possible for the grant.